Is There a Link Between Vitreous Cortex Remnants and Anatomic Outcome of Vitrectomy for Primary Rhegmatogenous Retinal Detachment? - Assi A; Mansour AM; Charbaji AR; Battaglia Parodi M (Clinical Ophthalmology, 2023)
Alexandre Assi,1 Ahmad M Mansour,2 Abdul Razzak Charbaji,3 Maurizio Battaglia Parodi4 1Beirut Eye Clinic and VitreoRetinal Department, Beirut Eye Specialist Hospital, Beirut, Lebanon; 2Department of Ophthalmology, American University of Beirut, Beirut, Lebanon; 3Department of Statistics and Research Methodology, Lebanese American University, Beirut, Lebanon; 4Department of Ophthalmology and IRCCS Ospedale San Raffaele, University Vita-Salute, Milan, ItalyCorrespondence: Ahmad M Mansour, Department of Ophthalmology, American University of Beirut, POB 113-6044, Beirut, Lebanon, Tel +9613377633, Email ammansourmd@gmail.comPurpose: To study the anatomic outcome of leaving vitreous cortex remnants (VCR) during pars plana vitrectomy (PPV) for primary rhegmatogenous retinal detachment (RRD).Methods: The study comprised patients with RRD who had PPV by a single surgeon between January 2019 and December 2020 and followed for 6 months. After intravitreal injection of triamcinolone acetonide, the topographic pattern of VCR at the periphery (p) and macula (m) was divided into 2 types by extent: complete or 4 quadrants (pVCR4Q), and between 2 and 4 quadrants ≥ 2 quadrants (pVCR> 2Q), or by location > 1 inferior retinal quadrant (pVCR> 1InfQ), and at the macula (mVCR). Anatomical failure or retinal re-detachment within 6 months after surgery was the primary outcome measures. The occurrence of grade C proliferative vitreoretinopathy (PVR) and epiretinal membrane (ERM) were used as secondary outcome indicators.Results: A 6-month prospective follow-up was performed on 103 patients. pVCR4Q was detected in 31 eyes, pVCR> 2Q in 40 eyes, pVCR> 1InfQ in 40 eyes and mVCR in 54 eyes. Recurrent RRD developed in 9 (8.7%) eyes, PVR grade C in 6 (5.8%) eyes and ERM in 11 (10.7%) eyes. According to multivariate regression analysis, the existence of any type of VCR did not correlate with anatomical failure, PVR or ERM.Conclusion: The initial success rate of PPV and the growth of PVR or ERM do not appear to be impacted by keeping VCR.Keywords: vitreous cortex remnants, pars plana vitrectomy, primary rhegmatogenous retinal detachment, epiretinal membrane, proliferative vitreoretinopathy